Analytical study of notifiable diseases in Sri Lanka at Lady Ridgway Hospital for children during the period January - June 1989. - Senanayake, G.S (My University, 1989)
An attempt was made to evaluate the efficiency of the present notification system and it was found that only 38 per cent of cases had been reported by the lady ridgeway hospital and of that only 12 per cent had been investigated by the public health inspectors in the colombo district.This notification rate is similar to the rates of developed countries prior to introducing their new methods.Developed countries have used modern and expensive methods such at the toll-free telephone reporting system,the sentinel reporting system,the use of paid physicians and special public health personnel t ocanvass physicians etc.Developing countries cannot afford such expensive methods.Therefore those countries have to look for less expensive but more effective methods to improve their notification systems.